Practices and Perspectives of Traditional Bone Setters in Northern Tanzania. Issue 1 (16th June 2020) - Card, Elizabeth B.; Obayemi, Joy E.; Shirima, Octavian; Lazaro, Matayo; Massawe, Honest; Stanifer, John W.; Premkumar, Ajay; Sheth, Neil P.
Background: Traditional health practitioners remain a critical source of care in Tanzania, more than 50% of Tanzanians frequently using their services. With a severe shortage of orthopaedic surgeons (1:3.3 million Tanzanians) traditional bone setters (TBSs) could potentially expand access to musculoskeletal care and improve outcomes for morbidity as a result of trauma. Objective: We sought to identify the advantages and disadvantages of traditional bone setting in Tanzania and to assess potential for collaboration between TBSs and allopathic orthopaedic surgeons. Methods: Between June and July 2017 we interviewed six TBSs identified as key informants in the regions of Kilimanjaro, Arusha, and Manyara. We conducted semi-structured interviews about practices and perspectives on allopathic healthcare, and analyzed the data using a deductive framework method. Findings: The TBSs reported that their patients were primarily recruited from their local communities via word-of-mouth communication networks. Payment methods for services included bundling costs, livestock barter, and sliding scale pricing. Potentially unsafe practices included lack of radiographic imaging to confirm reduction; cutting and puncturing of skin with unsterile tools; and rebreaking healed fractures. The TBSs described past experience collaborating with allopathic healthcare providers, referring patients to hospitals, and utilizing allopathic techniques in their practice. All expressed enthusiasm in future collaboration with allopathic hospitals. Conclusions: TBSs confer the advantages of word-of-mouth communication networks and greater financial and geographic accessibility. However, some of their practices raise concerns relating to infection, fracture malunion or nonunion, and iatrogenic trauma from manipulating previously healed fractures. A formal collaboration between TBSs and orthopaedic surgeons, based on respect and regular communication, could alleviate concerns through the development of care protocols and increase access to optimal orthopaedic care through a standardized triage and follow-up system.